Comparative study of biogas production from animal wastes by anaerobic digestion - Soom, Solomon; Adebo, Adeyinka; Orsaa, James; Ishuwa, Miriam (International Journal of Biological Research, 2016)
This study compares biogas production from cattle dung, piggery faeces and poultry wastes under different environmental conditions by anaerobic digestion as a means of managing municipal solid wastes and was conducted in the Department of Biological Sciences, Benue State University, Makurdi from 1st August, 2011 to 13th December, 2011. A 6 Kg of each of waste was mixed with four litres of water and loaded into three locally constructed digesters. The biogas produced was measured using water displacement method after every 5 days. The result indicated that piggery feaces gave the highest yield of biogas (1.07 L/kg), followed by cattle dung (0.71 L/kg), with poultry wastes the least (0.42 L/kg) all under direct sunlight. This study shows that piggery droppings are the best substrate for biogas production and the best yield result when the process is carried out under direct sunlight. However, statistical analysis showed no significant difference in the biogas yield of these feed stocks at 5 % level of significance. Anaerobic digestion is recommended to be explored as an environmentally friendly technology for organic waste management.